Trend study of psychodrugs use in a municipality of Minas Gerais under geological risk (Revista Contexto & Saúde, 2023)
The objective of this study was to analyze trends in the consumption of psychotropics by users of the Brazilian public Health System (Sistema Único de Saúde) in a city under geological risk, (Congonhas, Minas Gerais, Brazil). A descriptive pharmacoepidemiologic study of the utilization of psychotropics (quantitative consumption study) was developed. A comprehensive descriptive analysis of psychotropic drugs dispensed in periods before (2018) and after (2019) the Brumadinho dam break was performed considering active ingredients and major therapeutic classes (antidepressants and benzodiazepines). The data were described according to sex and according to the neighborhood covered by the primary health care unit where the patients were followed up. The latter was also classified according to the risk of flood in case of dam break. The findings show an increase in the overall number and average number of dispensed units of antidepressants (0.6% and 5.2%, respectively). In contrast, there was a drop in the overall number and average number of dispensed units of benzodiazepines (7.2% and 3.3%, respectively). These findings can support the reorganization of the municipality’s pharmaceutical services in response to the new challenges posed by the disaster.